Prospek Keuangan Syariah di Era Ekonomi Digital : Tantangan dan Peluang Bank Syariah - Farhana, Nabila; Afni, Nur (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to describe the challenges and opportunities of Islamic banks in the prospects of Islamic finance in the era of the digital economy. The research method used is a qualitative approach with data sources consisting of primary data using interviews and secondary data with data relevant to the study. The results of the study show that the challenges faced by Islamic banks in this digital economy era are cybersecurity, updating community needs, the application of the principle of prudence and know your customer (KYC) which is still less than optimal, and the application of the digital economy among the community. The opportunities faced by Islamic Banks in this digital economy era are Indonesia is a country with the largest Muslim population in the world, Cybersecurity development, Responsive product innovation, and Increased regulation